Rho GTPases and their downstream effectors in megakaryocyte biology. (2nd January 2019) - Pleines, Irina; Cherpokova, Deya; Bender, Markus
Abstract: Megakaryocytes differentiate from hematopoietic stem cells in the bone marrow. The transition of megakaryocytes to platelets is a complex process. Thereby, megakaryocytes extend proplatelets into sinusoidal blood vessels, where the proplatelets undergo fission to release platelets. Defects in platelet production can lead to a low platelet count (thrombocytopenia) with increased bleeding risk. Rho GTPases comprise a family of small signaling G proteins that have been shown to be master regulators of the cytoskeleton controlling many aspects of intracellular processes. The generation of Pf4-Cre transgenic mice was a major breakthrough that enabled studies in megakaryocyte-/platelet-specific knockout mouse lines and provided new insights into the central regulatory role of Rho GTPases in megakaryocyte maturation and platelet production. In this review, we will summarize major findings on the role of Rho GTPases in megakaryocyte biology with a focus on mouse lines in which knockout strategies have been applied to study the function of the best-characterized members Rac1, Cdc42 and RhoA and their downstream effector proteins.